KAJIAN KEBUTUHAN DAN PENDAPATAN PARKIR PADA KAWASAN OBJEK WISATA PANTAI KELAN KABUPATEN BADUNG BALI - Rahmayanti, Ni Made Prisca; Sriastuti, Dewa Ayu Nyoman; Aryastana, Putu (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Badung Regency is one of the largest contributors to regional economic income, namely in the world of tourism, especially the South Badung area which is famous for its many beach tourism objects which attract many foreign and local tourists. Availability of parking spaces, of course, must have good parking services in order to optimally utilize the available parking space capacity. This research focuses on planning the need for parking space and parking revenue for two-wheeled vehicles and four-wheeled vehicles in the Kelan Beach tourist area, because parking is one of the supports for tourism so that visitors can feel comfortable and can realize an adequate parking pattern. The planned land area for parking two and four-wheeled vehicles at Kelan Beach is 2097.30 m² in total. The survey method used is the cordon count and patrol method. Characteristics of parking for two-wheeled vehicles include the highest volume, namely 461, accumulation of 141 vehicles, duration of 1.63 hours, capacity of 173, turnover rate of 0.18, index of 0.68 less than (<) 1.00, which means the need for parking is below capacity/sufficient, and four-wheeled characteristics include volume maximum of 163, accumulation of 33 vehicles, duration of 1.48 hours, capacity of 49, turnover rate of 0.23, index of 0.57 less than (<) 1.00 which means parking needs are below capacity and do not need expansion. The parking space requirements for two-wheeled and four-wheeled vehicles are 63 and 20 slots respectively. The parking layout at Kelan Beach tourist destination adopts a 90° angle pattern for both two-wheeled and four-wheeled vehicles, with respective parking space dimensions of 0.75 m x 2.00 m and 2.50 m x 5.00 m. The projected annual parking revenue is estimated at IDR.499,441,667.00, calculated based on fixed rates. Paving blocks are chosen for the parking surface, with a cost of IDR.441,345,000.00.